Strategic leadership and its readerships to administrative development among deans of colleges at Sumer University from the point of view of department heads and assistant deans Welcome - Dr. Abbas nahi kaid (Journal of College of Education, 2026)
This study aims to identify the level of strategic leadership practices and their relationship with administrative development among the deans of the colleges at the University of Sumer, from the perspective of assistant deans and heads of departments. Strategic leadership is considered one of the fundamental pillars for developing educational institutions and achieving their long-term goals, due to its effective role in directing resources and efficiently utilizing human capabilities. The researcher adopted the descriptive correlational approach as it suits the nature of the study. A sample was selected from assistant deans and heads of departments in the colleges of the University of Sumer. To collect data, a questionnaire was used, consisting of two main dimensions: strategic leadership and administrative development. The validity and reliability of the instrument were verified using appropriate statistical methods. The results indicated that the level of strategic leadership practices among the deans was moderate to high. It also showed a good level of administrative development in the surveyed colleges. Furthermore, the findings revealed a positive statistically significant correlation between strategic leadership and administrative development, indicating that enhancing strategic leadership practices directly contributes to In light of the findings, the study recommends supporting university leaders through specialized training programs in strategic leadership, promoting a culture of continuous development within colleges, and adopting modern administrative methods that contribute to improving institutional performance